The Sensitivity Of Evapotranspiration For Land Uses And Topography In Cerrado Biome – Brazil (Revista Espaço e Geografia, 2022)
Evapotranspiration (ET) is a crucial element in the spatiotemporal dynamics of moisture, energy, and heat, and is related to climatic, pedogeomorphological, and phytophysiognomic aspects of the landscape. Therefore, estimating ET requires dynamic and integrated temporal analysis with biophysical landscape factors. The study aimed to analyze the behavior of ET through the analysis of land use and land cover and topographic in time series. The Simple Algorithm for Evapotranspiration Recovery (SAFER) model was used to obtain the variable ET in the periods of 01/21, 02/22, 05/13 and 06/30/2019 (variables). A database of explanatory covariates was constructed, including land use and land cover, satellite image data (Landsat-8) and digital elevation model (SRTM). The values of variables and covariates were extracted into a grid of points and separated for three altimetric conditions, and the linear Gaussian Models (GLM) were applied to the point data. The most explanatory spectral covariates for the ET variation were Albedo and Surface Temperature. And the covariates related to topography were Digital Elevation Model and Topographic Moisture Index. In general, the wet period presents a higher ET rate (2.06 mm d-¹). Forests generated the highest ET regardless of period (1.62 mm d-¹ to 4.03 mm d-¹). Elevated topography also influences the increase in ET in relation to the same lower altimetry classes (A2 and A3). This influence is associated with the altitude dynamics and intrinsic elements of the region, such as the marshy environment in the A3 region, where the highest ET values occurred. This work stands out from its peers for addressing the influence of landscape aspects on the knowledge of evapotranspiration variation, a vanguard theme in the scope of spatial analysis.